Construct validity and internal consistency of the Patient Health Questionnaire-9 (PHQ-9) depression screening measure translated into two Ugandan languages - Miller, Amanda P.; Silva, Cristina Espinosa da; Ziegel, Leo; Stephen, Mugamba; Kyasanku, Emma; Bulamba, Robert M.; Wagman, Jennifer A.; Ekstromc, Anna Mia; Nalugoda, Fred; Kigozi, Grace; Nakigozi, Gertrude; Kagaayi, Joseph; et al. (Psychiatry Research Communications, 2021)
In Uganda, depression is a major public health issue. Psychometric assessment of translated depression measures is critical to public health planning to ensure proper screening, surveillance, and treatment of depression and related outcomes. We examined aspects of the validity and reliability of the Patient Health Questionnaire-9 (PHQ- 9) translated into Luganda and Runyoro among Ugandan adolescents and adults. Data from the ongoing AMBSO Population Health Surveillance study were analyzed from the Wakiso and Hoima districts in Uganda. Descriptive statistics were calculated for the overall sample and stratified by translated language. Construct validity was assessed for each translated scale using confirmatory factor analysis for ordinal data. The internal consistency of each translated scale was assessed using Cronbach's alpha, McDonald's omega total and omega hierarchical. Both the Luganda- and Runyoro-translated PHQ-9 had similar sample means (3.46 [SD ¼ 3.26] and 3.58 [SD ¼ 3.00], respectively), supported a single-factor structure, and demonstrated satisfactory internal consistency (Cronbach's alpha of 0.73 and 0.72, respectively). Our preliminary findings indicate that the Luganda and Runyoro translations of the PHQ-9 had satisfactory construct validity and internal consistency in our sample. Future studies should expand on this promising work by assessing additional psychometric characteristics of these translated measures in other communities in Uganda.
Keywords: Factor analysis; Reliability; Sub-Saharan Africa; Luganda; Runyoro